High risk of fall, poor physical function, and low grip strength in men with fracture—the STRAMBO study. Issue 3 (19th November 2015) - Szulc, Pawel; Feyt, Clément; Chapurlat, Roland
Abstract: Background: Several studies assessed the association of prevalent fractures with muscle mass, strength, and physical capacity in men. Clinical impact of these associations is not clear, and they could be influenced by confounders. Our aim was to assess the association of the prevalent fractures with muscle strength, physical function, and the risk of subsequent falls in older men after adjustment for muscle mass and potential confounders. Methods: In a cohort of 890 men aged 50 and older, we assessed appendicular skeletal muscle mass (ASM) by DXA, grip strength, physical function (chair stands, static, and dynamic balance). Relative ASM (RASM) was calculated as ASM / (height) 2 . Then, 813 men aged 60 and over were followed up prospectively for 5 years and 144 sustained >1 incident falls. All the analyses were adjusted for lifestyle factors, co‐morbidities, and hormones known to influence muscle and physical function. Results: Low leisure physical activity, very high occupational physical activity, Parkinson's disease, diabetes mellitus, low apparent free testosterone concentration (AFTC), as well as Grade 2 and 3 vertebral fractures and multiple fractures were associated with lower grip strength when adjusted for confounders including upper limb RASM. Low leisure physical activity, very high occupational physical activity, diabetes mellitus, prior stroke, low AFTC and 25‐hydroxycholecalciferol, high C‐reactive protein, vertebral fractures, and non‐vertebral fractures were associated with poor physical function (lowest quintile of the score of tests) when adjusted for confounders including lower limb RASM. Grade 2 and 3 and multiple vertebral fractures were associated with twofold higher risk of multiple falls after adjustment for confounders. Men having multiple fractures had a twofold higher risk of multiple falls after adjusting for confounders. In multivariable models, risk of falls increased proportionally to the increasing severity and number of vertebral fractures as well as to the increasing number of all fractures. Conclusions: In older men, Grade 2 and 3 vertebral fractures and multiple vertebral and non‐vertebral fractures are associated with lower grip strength, poor physical function, and higher risk of multiple falls after adjustment for multiple confounders. This suggests a real direct association. One fracture can initiate a vicious circle leading to another fracture; thus, patients with fractures need physical therapy regardless of their general health status.